Application of Full 32 Factorial Design in Formulation and Optimization of Hydrodynamically Balanced System of Ketorolac Tromethamine - Asane, Dr. G. S. (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: The primary objective of this research work was to design a hydrodynamically balanced system (HBS) of ketorolac tromethamine based on the combination of swelling and effervescence mechanism that would result in minimum floating lag time (FLT), remain buoyant for extended period, and sustain the drug release for 12 h. Materials and Methods: HBS tablets of ketorolac tromethamine were prepared by wet granulation method using 32 full factorial design, where amount of hydroxypropyl methylcellulose K4M (X1) and sodium bicarbonate (NaHCO3) (X2) was taken as independent variables. The responses studied were Y1 (hardness), Y2 (FLT), Y3 total floating time (TFT), Y4 (swelling index [SI] in pH1.2), and Y5 (t80%) by plotting response surface graph and contour plots. Results: The FLT of prepared batches was in the range of 35.24 ± 0.04–116 ± 0.06 s and the minimum FLT was shown by OF-9 (35.24 s) batch. The TFT of all batches showed buoyancy and intactness for 24 h. The swelling in pH 1.2 at 8 h ranged between 47.80 ± 0.89 and 54.33 ± 0.11 with a significant difference (P < 0.0001). In vitro drug release study revealed that more than 95% of drug was released in 12 h and OB-2 showed 10 h to release 80% of the drug. The analytical characterization revealed the compatibility of drug with excipient and polymers. The stability studies performed for 6 months for OF-7 and OF-8 batches showed no change in physicochemical properties of drug and there was no significant difference (P < 0.05) in drug release. The response surface graph and contour plots showed the effect of variables on responses such as hardness (Y1), SI (Y4), and time taken for 80% of drug release (t80%)(Y5) which were found to be positively influenced by X1 and ANOVA for response surface quadratic model was found to be significant (P < 0.0001). The FLT (Y2) and TFT (Y3) were found to be affected by X2 and ANOVA for the response surface quadratic model was found to be significant (P < 0.05). Conclusion: From all the formulations, OF-8 showed ideal results in the form of hardness, FLT, TFT, SI, and time taken for 80% of drug release (t80%) and stability based on which it can be selected for in vivo studies.